Latitudinal variation in soil biota: testing the biotic interaction hypothesis with an invasive plant and a native congener. Issue 12 (December 2018) - Lu, Xinmin; He, Minyan; Ding, Jianqing; Siemann, Evan
Abstract Soil biota community structure can change with latitude, but the effects of changes on native plants, invasive plants, and their herbivores remain unclear. Here, we examined latitudinal variation in the soil biota community associated with the invasive plantAlternanthera philoxeroides and its native congenerA. sessilis, and the effects of soil biota community variation on these plants and the beetleAgasicles hygrophila . We characterized the soil bacterial and fungal communities and root-knot nematodes of plant rhizospheres collected from 22 °N to 36.6 °N in China. Soil biota community structure changed with latitude as a function of climate and soil properties. Root-knot nematode abundance and potential soil fungal pathogen diversity (classified with FUNGuild) decreased with latitude, apparently due to higher soil pH and lower temperatures. A greenhouse experiment and lab bioassay showed native plant mass, seed production, and mass of beetles fed native foliage increased with soil collection latitude. However, there were no latitudinal patterns for the invasive plant. These results suggest that invasive and native plants and, consequently, their herbivores have different responses to latitudinal changes in soil-borne enemies, potentially creating spatial variation in enemy release or biotic resistance. This highlights the importance of linking above- and below-ground multitrophic interactions to explore the role of soil biota in non-native plant invasions with a biogeographic approach.